Targeting apoptosis pathways in cancer therapy - Ghobrial, Irene (Henry Stewart Talks, 2007)
Apoptosis pathways, Pathways regulating the intrinsic and extrinsic pathways, ovel therapeutic agents in cancer therapy that target the apoptosis pathways and the modulators of apoptosis
Archived at 2020/01/15